Answer:
an = -7 × [tex](-2/3)^{n-1}[/tex]
Step-by-step explanation:
Given data
numbr = n
series = -7, 14/3 , -28/9, 56/27, -112/81 ......................
to find out
a formula for the general term an
solution
we know first term is = -7
second term = 14/3
third term = -28/9
fourth term = 56/27
and so on
so the ratio between these consecutive term i.e second term /first term and third term /second term and fourth term / third term and so on
ratio are = (14/3)/ -7 and (-28/9)/(14/3) and (56/27) / (-28/9) and so on
ratio are = (-2/3) and (-2/3 ) and (-2/3 ) / (-2/3 ) and so on
here we can see that all ration are same so that an of sequence with ratio -2/3 therefor general formula is for this sequence is given below i.e
an = first term × n[tex]r^{n-1}[/tex]
here r is ratio i.e. -2/3 and n is series 1, 2, 3, 4, 5, 6 ............ an so on
so
an = -7 × [tex](-2/3)^{n-1}[/tex]